Knowledge and Attitude Toward One Stop Crisis Center Among Students Studying in Selected Nursing College in Puducherry - L. Loganandham; Valavala, Mani Sandeep; S. Priyadharshini; R. Revathy; T. Nanthini; Chitra, A. Felicia (Indian Journal of Nursing Sciences, 2024)
Introduction: One Stop Crisis Center (OSCC) is an integrated health-care model that aims to provide comprehensive care to women experiencing physical, emotional, and sexual violence. The multilevel crisis interventions provided in OSCC include identification, diagnostic and therapeutic care, counseling and emotional support, legal support, medical reporting as well as provision of temporary shelter. Aim: This study aimed to assess the level of knowledge and attitude toward the One Stop Crisis Center (OSCC) among nursing students. Materials and Methods: A quantitative research approach was used. A descriptive cross-sectional research design was used to assess the level of knowledge and attitude toward OSCC. One hundred students were selected using a purposive sampling technique. A semistructured and self-administered questionnaire was used to assess the level of knowledge and attitude regarding OSCC among nursing students. The purpose of the study was explained to all the samples and the data were collected. Descriptive and inferential statistics wereused to analyze the data. Results: The study results revealed that out of 100 subjects, regarding their level of knowledge, only 10% had adequate knowledge of OSCC. Moreover, regarding the attitude around 91% of students had a favorable attitude toward the services of OSCC. There is a statistically significant association between the level of knowledge and attitude with gender at P < 0.001 level. Conclusion: The study concluded that the nursing students have moderate knowledge and favorable attitudes toward the services of OSCC. Nursing students should be aware of OSCC services and provide integrated support, including medical, legal, psychological, and counseling services to find against any forms of violence against women (VAW).